Analisis Pemanfaatan Platform Social Commerce untuk Peningkatan Omzet Penjualan UMKM Kerajinan Lokal di Kabupaten Bulukumba - Idrus, Imriani; Farida, Farida (Universitas Proklamasi 45, 2025)
The strategy of using social commerce is essential for local craft MSMEs to face competition and grow their market. This study aims to analyze the use of social commerce platforms to increase sales turnover of local craft MSMEs in Bulukumba Regency. The research method used a mixed methods approach with quantitative analysis through questionnaires and qualitative analysis through observation and in-depth interviews. Data were analyzed using descriptive techniques, multiple linear regression tests, and data triangulation. The results showed that the use of social commerce has a positive and significant influence on increasing sales turnover. The most effective platforms were Instagram, WhatsApp Business, Facebook, and Google My Business. The success of these platforms is greatly influenced by the frequency of use, content, branding strategies, and interaction with customers. Optimal strategies for MSMEs include consistent visual content, storytelling, and live selling on Instagram/Facebook; utilization of quick replies, catalogs, and personalized service features on WhatsApp Business; and profile optimization, photo updates, and customer reviews on Google My Business. This study concludes that social commerce is not only a promotional tool but also an effective strategy to expand market reach and increase the competitiveness of MSMEs.